2013
DOI: 10.1038/eye.2013.103
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic conjunctival bacteria associated with systemic co-morbidities of patients undergoing cataract surgery

Abstract: Purpose To identify the risk of patients undergoing cataract surgery of having pathogenic conjunctival bacteria associated with their systemic co-morbidities. Methods Retrospective study of consecutive patients undergoing their first cataract operation from July 2005 to April 2010. Their preoperative conjunctival bacteria were cultured, identified, and classified in bacterial groups. Their co-morbidities were defined from their clinical data and the answers to systematic questions asked in the anaesthetic eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 48 publications
0
33
1
Order By: Relevance
“…A high detection rate of conjunctival bacteria among patients with systemic disease has been previously reported. 6,8 The reason why diabetes was not a risk factor in our study is unknown. In an epidemiological study of Japan (the Hisayama study), the prevalence of diabetes at 40-79 years was 24.0% for men and 13.4% for women.…”
Section: Eyementioning
confidence: 94%
See 4 more Smart Citations
“…A high detection rate of conjunctival bacteria among patients with systemic disease has been previously reported. 6,8 The reason why diabetes was not a risk factor in our study is unknown. In an epidemiological study of Japan (the Hisayama study), the prevalence of diabetes at 40-79 years was 24.0% for men and 13.4% for women.…”
Section: Eyementioning
confidence: 94%
“…Fernández-Rubio et al 8 reported that increased age and the male sex were associated with the Corynebacterium detection rate in conjunctiva. Corynebacterium grows easily in lipid-rich environments.…”
Section: Eyementioning
confidence: 99%
See 3 more Smart Citations